Unveiling the Potential of Polyphenols as Anti-Amyloid Molecules in Alzheimer’s Disease - Kabir, Eva R.; Chowdhury, Namara Mariam; Yasmin, Hasina; Kabir, Md. Tanvir; Akter, Rokeya; Perveen, Asma; Ashraf, Ghulam Md.; Akter, Shamima; Rahman, Md. Habibur; Sweilam, Sherouk Hussein (Current Neuropharmacology, 2023)
Alzheimer’s disease (AD) is a devastating neurodegenerative disease that mostly affects the elderly population. Mechanisms underlying AD pathogenesis are yet to be fully revealed, but there are several hypotheses regarding AD. Even though free radicals and inflammation are likely to be linked with AD pathogenesis, still amyloid-beta (Aβ) cascade is the dominant hypothesis. According to the Aβ hypothesis, a progressive buildup of extracellular and intracellular Aβ aggregates has a significant contribution to the AD-linked neurodegeneration process. Since Aβ plays an important role in the etiology of AD, therefore Aβ-linked pathways are mainly targeted in order to develop potential AD therapies. Accumulation of Aβ plaques in the brains of AD individuals is an important hallmark of AD. These plaques are mainly composed of Aβ (a peptide of 39-42 amino acids) aggregates produced via the proteolytic cleavage of the amyloid precursor protein. Numerous studies have demonstrated that various polyphenols (PPHs), including cyanidins, anthocyanins, curcumin, catechins and their gallate esters were found to markedly suppress Aβ aggregation and prevent the formation of Aβ oligomers and toxicity, which is further suggesting that these PPHs might be regarded as effective therapeutic agents for the AD treatment. This review summarizes the roles of Aβ in AD pathogenesis, the Aβ aggregation pathway, types of PPHs, and distribution of PPHs in dietary sources. Furthermore, we have predominantly focused on the potential of food-derived PPHs as putative anti-amyloid drugs.
Keywords: Alzheimer’s disease